Challenges and Opportunities to Achieve Digital Maturity in Healthcare: A Literature Review - Putra, Dewa Ngakan Gde Wahyu Mahatma; Khoiri, Abu; Naya, Aulia Riswanti (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
Digital transformation in the healthcare sector offers many benefits, but achieving it requires good digital maturity. This study aimed to identify the role of digital maturity in innovative healthcare, challenges, opportunities, and recommendations that could be applied in an effort to achieve digital maturity. This study used a systematic literature review method by extracting articles from the Scopus, PubMed, and Google Scholar databases in the last 10 years using the keywords "digital maturity", "healthcare", "hospital", and "health." The selected articles were in English and available open-access, which were then synthesized theoretically and presented in narratives. The results of the study showed significant benefits of digital maturity, including improved diagnostic accuracy, resource optimization, and patient engagement. However, obstacles such as limited funding, diverse digital literacy, and regulatory challenges were still found. The study provided recommendations to address barriers and emphasized the need for tailored digital solutions and supportive regulations for health practitioners and policymakers in an effort to increase digital maturity in the healthcare sector.